2002
DOI: 10.1029/2001jb000920
|View full text |Cite
|
Sign up to set email alerts
|

Deformation of polycrystalline MgO at pressures of the lower mantle

Abstract: [1] Room temperature investigations on the shear strength, elastic moduli, elastic anisotropy, and deformation mechanisms of MgO (periclase) are performed in situ up to pressures of 47 GPa using radial X-ray diffraction and the diamond anvil cell. The calculated elastic moduli are in agreement with previous Brillouin spectroscopy studies. The uniaxial stress component in the polycrystalline MgO sample is found to increase rapidly to 8.5(±1) GPa at a pressure of 10(±1) GPa in all experiments. Under axial compre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
177
6

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 216 publications
(200 citation statements)
references
References 77 publications
(141 reference statements)
17
177
6
Order By: Relevance
“…In order to interpret our experimental textures we use the viscoplas-A c c e p t e d M a n u s c r i p t tic self-consistent polycrystal plasticity model (Lebensohn and Tomé, 1993) to simulate texture evolution in cubic perovskite polycrystal deformed by slip under axial compression. The experimental texture pattern of CaSiO 3 perovskite in axial compression is similar to textures obtained for MgO (Merkel et al, 2002), a cubic minerals with low temperature slip systems of {110}<110>. This is the same slip system that has been proposed for cubic perovskites at low temperature (Poirier et al, 1989) and observed at high temperature in CaTiO 3 (Besson et al, 1996) and SrTiO 3 (Wang et al, 1993).…”
Section: Texturesupporting
confidence: 60%
See 2 more Smart Citations
“…In order to interpret our experimental textures we use the viscoplas-A c c e p t e d M a n u s c r i p t tic self-consistent polycrystal plasticity model (Lebensohn and Tomé, 1993) to simulate texture evolution in cubic perovskite polycrystal deformed by slip under axial compression. The experimental texture pattern of CaSiO 3 perovskite in axial compression is similar to textures obtained for MgO (Merkel et al, 2002), a cubic minerals with low temperature slip systems of {110}<110>. This is the same slip system that has been proposed for cubic perovskites at low temperature (Poirier et al, 1989) and observed at high temperature in CaTiO 3 (Besson et al, 1996) and SrTiO 3 (Wang et al, 1993).…”
Section: Texturesupporting
confidence: 60%
“…Solid lines are guide to eyes through the data. M a n u s c r i p t (Merkel et al, 2003), open triangles results for MgO (Merkel et al, 2002), grey diamonds results for olivine (Uchida et al, 1996), open diamonds results for ringwoodite (Kavner and Duffy, 2001), and open circles results for SiO 2 (Shieh et al, 2002). Lines are guides to the eyes through the experimental data.…”
Section: A N U S C R I P Tmentioning
confidence: 99%
See 1 more Smart Citation
“…Local background subtraction and polarization correction is also applied to the measured intensities [11]. Diffraction intensities were extracted with FIT2D into a multicolumn ASCII spread sheet [12], where each column corresponds to an intensity distribution along the azimuth for a particular 2θ value. The peak positions were identified from full profile analysis using the GSAS refinement code [13] and intensity versus azimuth data for particular reflections were extracted.…”
Section: Discussionmentioning
confidence: 99%
“…1͒. Most of these experiments are only possible because of the use of x-ray transparent gaskets, consisting of amorphous B inserts [6][7][8][9] or Be 3,4 that allow the collection of x-ray diffraction data from samples perpendicular to the loading axis. Radial diffraction has also been used to study texture and crystallographic preferred orientations ͑CPOs͒ in plastically deformed materials 10 by measuring intensity variations along the Debye rings.…”
Section: Introductionmentioning
confidence: 99%